PENGARUH KONTRIBUSI, KLAIM, DAN UNDERWRITINGDANA TABARRU' TERHADAP TINGKAT LABA DENGAN RISK BASED CAPITAL SEBAGAI VARIABEL MODERASI - Devara Alvian Baihaqi, (2023)
Islamic insurance must be able to consider changes in the company's performance, particularly internal elements that have an impact on earnings. According to the sharia insurance industry's overall profit development, the trend is downward. There are a number of things that can impact an Islamic insurance company's profitability. The purpose of this study is to determine the contribution, claims, and underwriting of tabarru' funds and the moderation of risk-based capital on the profit of Islamic life insurance companies for the years 2017-2021. This study employs a quantitative descriptive methodology and secondary data from the financial records of every audited company as well as OJK statistics. This study uses panel data regression with moderating variables. The results of this study found that the contribution, claims and underwriting of the tabarru funds have a significant effect on the level of profit. Whereas for the partial test of claims it has a significant negative effect on the level of profit, the contribution and underwriting of tabarru funds does not have a significant effect on the level of profit. The relationship between contributions, claims, and underwriting of tabarru funds and profit levels cannot be moderated by the Risk Based Capital moderation variable.